Finite Element Analysis of RC Tapered Beams under Cyclic Loading - Harba, Ibrahim S. I.; Abdulridha, Abdulkhalik J. (Al-Nahrain Journal for Engineering Sciences, 2017)
This paper presents a numerical investigation to study the effect of variations in displacement history sequence and magnitude on cyclic response of RC tapered (haunched) beams (RCHBs).Five simply supported RCHBs (four haunched and one prismatic) were selected from experimental work carried out by Aranda et al. The selected variables included were five loading history types. The first part of this study focused to verify the finite element analysis with selected experimental work and the second part of this study focused too studying the effect of varying in loading history to the response of RCHBs. The finite element code Abaqus was used in the modeling. The adopted cyclic simulation performance of the selected beams using the plastic- damage model for concrete developed by Lubliner and Lee & Fenves. The constitutive model of plain concrete describing the uniaxial compression response under cyclic loading proposed by Thorenfeldt, and the uniaxial tension response follows the softening law proposed by Hordijk was used in the modeling. Menegotto-Pinto model was used to simulate the steel response. Model verification has shown A good agreement to the selected experimental work. The variations in loading history will decrease the ultimate load and corresponding deflection with increase in the number of cycles at ultimate load.